Pengaruh Kesadaran Hemat Energi Terhadap Perilaku Hemat Energi - Rizky Bachtiar; Azmi Al Bahij; Nadiroh Nadiroh; Sihadi Sihadi (Jurnal PGSD, 2020)
This research is motivated by the low awareness of students in energy-efficient behavior, awareness of the Indonesian people needs to be grown to realize that energy reserves are no longer abundant, so far there has been a view in the community that our energy sources are abundant so that their behavior in consuming energy becomes wasteful and inefficient. The aim is to find whether there is an effect of energy-saving awareness on energy-saving behavior and how much influence it has. The research was conducted at SDN Pondok Aren 04 with a population and a sample of 155 students. This type of research used quantitative methods with a survey model. Data collection techniques used by researchers are questionnaires, documentation, and observation. The instrument used was a questionnaire, with a total of 40 questions, each with 20 variable X statements and 20 variable Y statements. The data analysis test technique was a simple regression test. The results of this study were obtained, namely 1) that there is an influence between energy saving awareness on energy saving behavior; 2) based on data obtained from the questionnaire the influence of energy saving awareness on Rsquare energy saving behavior of 0.605 or KD = 0.605X100% = 60.5%. While 39.5% is influenced by other variables. The results of this study are expected to give more information to teachers or education to students about energy-saving behavior and make students more aware of the importance of behaving energy-saving behavior.